2019
DOI: 10.3390/nano9091219
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanate-Functionalized Mesoporous Silica Nanoparticles as Building Blocks for the Design of Nanovehicles with Optimized Drug Release Profile

Abstract: A straightforward methodology for the synthesis of isothiocyanate-functionalized mesoporous silica nanoparticles (MSNs) by exposure of aminated MSNs to 1,1′-thiocarbonyldi-2(1H)-pyridone is reported. These nanoparticles are chemically stable, water tolerant, and readily react with primary amines without the formation of any by-product. This feature allows the easy modification of the surface of the nanoparticles for tuning their physical properties and the introduction of gatekeepers on the pore outlets. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The isothiocyanate group is known to readily react with free amino groups forming stable thiourea linkages, which have been widely used to couple biomolecules, dyes, and nanostructures with a click chemistry approach. 39,40 On the other hand, the nitrilotriacetic acid (NTA) terminus of the linker can be activated for proteins containing six adjacent histidine residues (His-tagged proteins), by complexation of Ni 2+ ions, as previously reported (Fig. 2).…”
Section: Synthesis and Characterization Of Gnrs@chit-dec Ex Vivomentioning
confidence: 68%
“…The isothiocyanate group is known to readily react with free amino groups forming stable thiourea linkages, which have been widely used to couple biomolecules, dyes, and nanostructures with a click chemistry approach. 39,40 On the other hand, the nitrilotriacetic acid (NTA) terminus of the linker can be activated for proteins containing six adjacent histidine residues (His-tagged proteins), by complexation of Ni 2+ ions, as previously reported (Fig. 2).…”
Section: Synthesis and Characterization Of Gnrs@chit-dec Ex Vivomentioning
confidence: 68%
“…Furthermore, mesoporous MCM-41 is a typical molecular sieve mesoporous silica material with the regular and hexagonal arrangement of SiO 2 that has an enhanced specific surface area, good mechanical and thermal stability, and a governable pore size [28], possessing all the advantages of MSNs, with a synthesis method that is simple and efficient [29]. Studies have reported that loading EOs to mesoporous silica nanoparticles can improve its bioavailability, and achieve controlled release in a food area like targeted drug release [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…(B) isothiocyanate-functionalized mesoporous silica nanoparticle made of TEOS and 3-aminopropyl triethoxysilane. Reprinted from [9].…”
Section: Introductionmentioning
confidence: 99%